The physical activity and sedentary behavior among pregnant women in Macao: A cross-sectional study. - Ka Chon Mok; Ming Liu; Xin Wang (PLoS ONE)
Objective The current investigation sought to elucidate the prevalence and contributing factors of sedentary behavior among pregnant women in Macao, a densely populated region characterized by a distinctive fusion of Eastern and Western cultures and a thriving global economy. Methods Through a cross-sectional study design, a total of 306 expectant mothers were recruited via various social media platforms and completed a sociodemographic questionnaire alongside the Chinese version of the Pregnancy Physical Activity Questionnaire. Results The findings revealed that sedentary activities accounted for a relatively small proportion (7.8%) of the participants' total activity energy expenditure. Interestingly, employment status emerged as a significant determinant, with employed pregnant women exhibiting a 57.9% lower risk of being sedentary compared to their unemployed counterparts. Moreover, multiparous women (those with two or more children) were approximately 9 times more likely to meet moderate-intensity activity standards than nulliparous women. Conclusion These insights highlight the importance of tailoring physical activity interventions to address the specific needs and challenges faced by primiparous women and those who are unemployed during pregnancy, with a view to enhancing education on the potential hazards associated with sedentary habits and promoting active lifestyles within this unique sociocultural context.